The river – city relationship: case study of the espinharas river in the city of Patos/PB - Silva, Emmanoel Marques da; Albuquerque, Sheila Rodrigues de; Carvalho , Gabriel Lincoln Lopes; Silva , Paulo Roberto de Oliveira; Silveira, José Augusto Ribeiro da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Since the emergence of cities, their relationship with water resources has been evident, especially with rivers, which have been responsible for the growth and development of numerous cities throughout history. In this historical construction, the river-city relationship has faced ups and downs, and today it is a worrying and contradictory reality, where urban processes are characterized as one of the main causes of existing problems. Thus, the proposal of this research aims to understand the relationship between cities and the river, and for this, an object of study was selected - the Espinharas River, located in the city of Patos, in Paraíba. The method of analysis chosen was field research, aiming at loco visits, surveys, and the creation of conceptual maps, for the characterization of the riparian zones and understanding of their relationship with the city. As results and conclusions, it was verified that urban rivers face real problems due to urbanization processes, and that planning measures should be applied to obtain the re-establishment of the riveting that applies to the city of Patos and the Espinharas River, which are inserted in this context.